Exploring Data-Driven Culture in The Construction Industry: Insights from Industry Practitioners - Muhammad Adib Hashim; Che Khairil Izam Che Ibrahim; Nurul Elma Kordi (Online Journal for TVET Practitioners, 2025)
In previous studies, attributes, sub-attributes and indicators of data driven culture has been studied within the organizations specifically for the construction industry. Nevertheless, there has been no further study conducted on the perspective of construction industry personnels about their viewpoint on the indicators associated with a data-driven culture. Thus, the aim of this research is to cover the gap of data by identifying “perspectives” of industry practitioners on data driven culture in the construction industry. The study started by using Systematic Literature Review (SLR) as a method of literature study, then obtaining validation from 18 practitioners from construction industry analysed by using thematic analysis, and Relative Importance Index (RII). The highest RII value recorded based on each sub-attributes listed are: D1 – knowledge and expertise, ID3 – availability of fund, C4 – competency, U7 – building model exploration, P1 – register based statistics, P3 – information extraction and P8 – control strategy. The finding of this study benefit construction industry stakeholders to become more skilled, cooperative and dynamic through the documented acknowledgment of their perspective as practitioners in digital construction as emphasized in Malaysian Digital Construction and Industry 4.0 Roadmap 2020-2025.